Disseminated cryptococcal infection in a patient with treatment-naïve chronic lymphocytic leukemia (CLL). (2019) - Suleman, Adam; Padmore, Ruth; Faught, Carolyn; Cowan, Juthaporn
Abstract: We report a case of disseminated cryptococcosis in a treatment-naïve chronic lymphocytic leukemia (CLL) patient. A 60-year-old man presented with a two-week history of intermittent fevers, frontal headaches, night sweats, weight loss and multiple pink papules on hands and face. Cryptococcemia was found by blood culture unexpectedly. Further investigation confirmed cryptococcal meningitis and skin disease. He responded to two week amphotericin B and flucytosine followed by four-week amphotericin B and fluconazole, three-month high dose fluconazole (800 mg/day), and maintenance fluconazole (400 mg/day) thereafter. CSF pleocytosis persisted until day 203 while cryptococcal antigen in the CSF persisted at day 334 of treatment.